تمكين الشباب الإماراتي بواسطة المشاريع الصغيرة والمتناهية الصغر: دراسة ميدانية - حسن، شريفة محمد حسين; الحوراني، محمد عبدالكريم (جامعة بغداد - كلية الآداب, 2023)
إن الدور المهم الذي تؤديه المشاريع الصغيرة والمتناهية الصغر واضح في جميع أنحاء العالم. تترك هذه المشاريع بصماتها على المشهد الاقتصادي نظرا لأهميتها الاستراتيجية في إعادة هندسة القطاعات الصناعية والتجارية والإنتاجية وتحقيق التنمية ودعم الاقتصاد فضلا عن دورها في تمكين أفراد المجتمع بما فيهم الشباب. إذ إن تمكين الشباب وتذليل كل العقبات للاستفادة من طاقاتهم وإبداعاتهم يمثل رؤية وطنية مستدامة لدولة الإمارات العربية المتحدة. هدفت هذه الدراسة إلى التعرف على وجهات نظر الشباب المستفيدين من هذه الصناديق والمؤسسات ومدى فاعليتها ودورها في تمكينهم، وبناء على ذلك، جرت صياغة سبعة أسئلة بحثية للإجابة عنها. وقد استخدمت الدراسة المنهج الكمي، إذ جمعت البيانات الكمية من خلال استخدام استبانة وزعت على (٥٠٣) شاب مستفيد من المشاريع التي تدعمها المؤسسات والصناديق. كما أظهرت الدراسة جملة من التحديات والمشكلات التي تواجه الشباب أصحاب المشاريع ومؤسسات وصناديق الدعم. وفي الأخير، أوصت الدراسة بجملة من النقاط التي يمكن أن تسهم في الارتقاء بمستوى تمكين الشباب في الدولة بما في ذلك مراجعة السياسات الحالية وإنشاء منظومة شاملة لتمكين الشباب في الدولة تشارك فيها جميع الأطراف في المجتمع على أن تتضمن هذه المنظومة تيسير إجراءات إنشاء مشروعات الشباب وتعزيز مهارات ريادة الأعمال وإدارة المشاريع. The important role of micro and small enterprises is evident. These enterprises leave their marks on the economic scene due to their strategic importance in re-engineering the industrial, commercial and production sectors, achieving development and supporting the economy, as well as their role in empowering members of society, including the youth. Empowering youth and overcoming all obstacles to benefit from their energies and creativity represents a sustainable national vision for the United Arab Emirates. This study aimed to identify the views of the youth beneficiaries of these funds and institutions and their effectiveness. Accordingly, seven research questions were formulated to answer them. The study used the quantitative approach, where quantitative data was collected through the use of a questionnaire distributed to (503) young people benefiting from projects supported by institutions and funds. The study also revealed a number of challenges and problems facing young entrepreneurs and support institutions and funds. Finally, the study recommended a number of points that can contribute to raising the level of youth empowerment in UAE, including revising the current policies and establishing a comprehensive system for youth empowerment in which all parties in society participate, provided that this system includes facilitating procedures for establishing youth enterprises and enhancing youth skills of entrepreneurship and project management.
Keywords: المشروعات الاستثمارية -- إدارة المشاريع -- الأنشطة الاقتصادية -- تمكين الشباب -- المشاريع التنموية